MEDIA PEMBELAJARAN IPAS MATERI KERAGAMAN BUDAYA YANG DIKAITKAN DENGAN NILAI-NILAI KEARIFAN LOKAL DI SEKOLAH DASAR: TINJAUAN LITERATUR RIVEW - Hakimah, Nailul; Nasution; Gunansyah, Ganes (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
When learning takes place, students often have difficulty in understanding the material presented by the teacher. The use of learning media that is less varied is one of the causes of students not understanding the material, feeling bored, sleepy and bored when learning. This happens in one of the learning materials, namely about cultural diversity. Appropriate and interesting media is needed to overcome learning problems. Identifying suitable media to be used on cultural diversity material is the purpose of this research. This research collects articles from Semantic Scholar, and Google Scholar for the period 2019 to 2024 and uses a Systematic Literature Review (SLR). Although there are many media that can be used in learning IPAS on the subject of cultural diversity, according to this study, visual media and interactive digital media are the most widely used in primary school learning. This is because they are proven to be effective in helping students understand and appreciate cultural diversity from an early age. Visual media, such as posters and pictures, provide concrete images of various cultural elements, which make it easier for students to make connections with the material being taught. Meanwhile, interactive digital media allows students to be actively involved in teaching and learning activities, increase interest in learning, and develop critical and collaborative thinking skills. Keywords: Cultural Diversity; IPAS Learning; Learning Media; Elementary School